Malignant Bowel Obstruction in Ovarian Cancer Recurrence: The Role of Palliative Surgery in a Decision-Making Process - Eugenia De Crescenzo; Marianna Fontana; Giulia Dondi; Stefano Friso; Alessandro Bovicelli; Marco Di Stanislao; Marco Tesei; Alessandra De Palma; Pasquale Chieco; Matteo Rottoli; Paolo Bernante; Gloria Ravegnini; et al. (Clinical and Experimental Obstetrics & Gynecology)
Background: Malignant bowel obstruction (MBO) is often the latest stage in ovarian cancer (OC). The therapy of this condition ranges from medical waiting to surgery. The objective of this pilot study is to compare the two strategies so that we can provide a path forward for future studies. Methods: From 700 women diagnosed with OC in the database of the Division of Gynecologic Oncology we crossed the names of those admitted by the emergency services of the IRCSS Azienda Ospedaliero Universitaria of Bologna, Italy. We selected MBO patients with a history of OC as the only neoplastic condition and compared the results between medical conduct and surgery to restore intestinal transit. Results: Of the 700 women in our database, 36 were eligible for study according to the inclusion and exclusion criteria: 9 in surgery group and 27 in medical group. Surgical conduct (tumor biopsy and stoma) appears to be resolutory for the obstruction and have a better result than medical therapy regarding recurrence of MBO, despite the development of greater complications. Relapses of MBOs occurred in 11% of surgical patients and 44% of medical patients (p = 0.0714). Furthermore, after surgical treatment, five patients (55%) experienced postoperative complications; in four cases, severe anemia requiring blood transfusion, while one patient developed post-surgical sepsis, which evolved into multiple organ failure and death. Of the 9 patients treated surgically, 2 (22%) were given surgery as a first choice. In most cases (78%), surgery was decided upon when medical treatment failed. The only discriminative factor appears to be age. The length of hospitalization increased with the patient’s age (p = 0.0181) as statistically significant factors for a worse outcome in surgery. Conclusions: MBO requires complex and multidisciplinary management where different factors need to be considered before initiating surgical therapy. Future studies are needed to deal with this complex problem.